The Factors Affecting the Flow of Traffic During Rush Hour in Barangay Tungko Mangga San Jose Del Monte Bulacan: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Commuting means waking up before the sun even rises just so you can avoid traffic. It meansbracing yourself for the one-hour travel time- even without the traffic. Considering the highnumber of commuters, which exceeds the number of available public utility vehicles, as wellas the terrible traffic, the very thought of commuting to any place is a nightmare. Despite theFactor our government is making efforts to improve our position, such as the development of“Bagong Jeeps” (BEEP), the current state of our public transportation is deplorable. AsFilipinos are the ones who mainly use and facilitate these amenities, it can be said that thestate of the Philippines’ public transport system is a representation of the Filipino. The lack ofdiscipline that drivers have, which greatly contributes to the heavy flow of traffic, points back tohow Filipinos unknowingly cause the problems that they continuously gripe about.The result of the study about the factors affecting the flow of traffic during rush hour inBarangay Tungko Mangga San Jose Del Monte as regards the road condition is that theaverage composite mean is 2.85 and interpreted as agreeable. As regards the volume oftraffic, the average composite mean is 2.90 and interpreted as Agree. As regards the trafficenforcers' availability, the average composite mean is 3.00 and interpreted as Agree.The respondents' assessment of the factors affecting the flow of traffic is by utilizing thesidewalk, implementing no garage, no car policy, and utilizing pedestrian lanes andoverpasses. There are some proposed recommendations to further enhance the factorsaffecting the flow of traffic during rush hour, which include improving intersections, usingpublic transportation more than private transportation, and carpooling.
Keywords: Criminology